Structure of technical-tactical activities in table tennis - Munivrana, G.; Cavala, M.; Kondric, M.; Karkovic, N. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
For the purpose of determining the overall structure of technical-tactical elements in table tennis and evaluating their role in different playing zones on and around the table, a new measuring instrument (a questionnaire) was formulated that takes advantage of the expert knowledge of top, world class table tennis coaches. The results have showed that the overall structure of the technical-tactical elements forming the table tennis technique can be divided into three basic groups; a group of technical-tactical elements (A) used in the phase of preparing one`s own and disabling the opponent`s attack; a group of technical-tactical elements (B) used in the phase of attack and counterattack; and a group of technical-tactical elements (C) used in the phase of defence. The differences among the obtained groups of table tennis elements were determined by applying the Kruskal-Wallis test, while relations between the groups and their role in different playing zones on and around the table were analysed by comparing the average values of the experts` scores